Kerjasama Internasional Dalam Penegakan Hukum Pidana Internasional - Rizkianto, Kus (Universitas Pancasakti Tegal, 2021)
The purpose of the study is to examine the form of international cooperation in the enforcement of international criminal law. The occurrence of international cooperation is characterized by the existence of relations between subjects of international law that need each other. The development of international law and international criminal law in the 21st century has entered the century of integrated world of community in facing challenges and threats by disengaging from the reality of the interrelationship and attachment of a nation to objective conditions both culturally, ethnically, geographically and factors of the political system that develops in the country concerned so that international cooperation is indispensable in enforcing international criminal law or it can be said that it can be said that International cooperation is an important factor in the enforcement of international criminal law. Research Methods use a type of literature paradigmatic approach, secondary data sources, and data analysis using descriptive analysis. The results showed that there are forms of cooperation that can be carried out in the enforcement of international criminal law, especially human rights violations, including extradition, transfer of prisoners, mutual legal assistance, joint investigations, cooperation in conducting special investigation techniques, and transfer of criminal proceedings.